2019
DOI: 10.3390/pr7040207
|View full text |Cite
|
Sign up to set email alerts
|

Recycling of Carbon Fibers from CFRP Waste by Microwave Thermolysis

Abstract: With the growth of the use of carbon fiber-reinforced polymer (CFRP) in various fields, the recovery of carbon fibers from CFRP waste is becoming a significant research direction. In the present work, degrading epoxy resin and recycling carbon fibers from CFRP waste by microwave thermolysis and traditional thermolysis were studied. The carbon fibers were successfully recovered by thermolysis under an oxygen atmosphere in this study. The properties of the recovered carbon fibers were characterized by field emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 42 publications
(63 reference statements)
2
26
0
Order By: Relevance
“…However, currently, several research works are carried out to investigate the implementation of more cost-effective and efficient ways of CFRP recycling. For example, some authors propose using CFRP in the production of eco-efficient cementbased materials [12], and others study microwave thermolysis claiming to be more efficient compared to conventional thermolysis [21].…”
Section: Chinamentioning
confidence: 99%
“…However, currently, several research works are carried out to investigate the implementation of more cost-effective and efficient ways of CFRP recycling. For example, some authors propose using CFRP in the production of eco-efficient cementbased materials [12], and others study microwave thermolysis claiming to be more efficient compared to conventional thermolysis [21].…”
Section: Chinamentioning
confidence: 99%
“…At present, a variety of technologies for carbon fiber recovery from carbon fiber reinforced epoxy composites have been proposed. In Deng's paper [7], the degradation of epoxy resin in the CFRP waste and the recycling of carbon fiber were studied by microwave thermolysis and traditional thermolysis respectively. The effects of reaction temperature and reaction time on the recovery of carbon fiber were studied, and the properties of carbon fiber were characterized to compare the characteristics of the two methods.…”
Section: Application Of Microwave Heating In Waste Treatment and Dryingmentioning
confidence: 99%
“…The authors also proposed the mechanism of microwave separation, whereby the fibre was first heated via the antenna effect by microwave irradiation to gasify the resin, and then gasified resin was further decomposed by spark glow plasma between carbon fibres. Deng et al [ 18 ] compared carbon fibres recycling via microwave thermolysis and traditional thermolysis under a pure oxygen atmosphere and found 450 °C to be the optimum temperature. They also reported that microwave thermolysis saved 57% reaction time and increased recovery ratio by 15% compared to conventional thermolysis.…”
Section: Introductionmentioning
confidence: 99%